2013
DOI: 10.1002/phy2.41
|View full text |Cite
|
Sign up to set email alerts
|

Tulobuterol inhibits rhinovirus infection in primary cultures of human tracheal epithelial cells

Abstract: A transdermal patch preparation of the β2 agonist tulobuterol has been designed to yield sustained β2 agonistic effects and has been used as a long-acting β2 agonist (LABA) in Japan. LABAs reduce the frequency of exacerbations of chronic obstructive pulmonary disease and bronchial asthma. However, inhibitory effects of LABAs on the replication of rhinovirus (RV), the major cause of exacerbations, have not been demonstrated. To examine the effects of tulobuterol on RV replication and on the production of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(141 reference statements)
1
9
0
Order By: Relevance
“…cAMP increases endosomal pH by inhibiting an Na þ /H þ exchanger [29]. We demonstrated that formoterol increased the cAMP levels in HNE cells, which decreased the number of acidic endosomes, as previously reported for HTE cells [30]. Therefore, formoterol may inhibit the functioning of Na þ /H þ exchangers via the production of cAMP in cells.…”
Section: Discussionsupporting
confidence: 86%
“…cAMP increases endosomal pH by inhibiting an Na þ /H þ exchanger [29]. We demonstrated that formoterol increased the cAMP levels in HNE cells, which decreased the number of acidic endosomes, as previously reported for HTE cells [30]. Therefore, formoterol may inhibit the functioning of Na þ /H þ exchangers via the production of cAMP in cells.…”
Section: Discussionsupporting
confidence: 86%
“…Several reports showed that b 2 -AR stimulation mitigates NF-jB phosphorylation, nuclear translocation, DNA binding and transcriptional activity, in both immune (Farmer and Pugin, 2000;Herve et al, 2013;Hu et al, 2012;Loop et al, 2004;Loza et al, 2006;Mortaz et al, 2008;Strell et al, 2009;Yang et al, 2003) and non-immune cell types (Baouz et al, 2005;Yamaya et al, 2013) (For details refer to Table 1). In many cases NF-jB activity was measured via electrophoretic mobility shift assay (EMSA), which assesses DNA binding, or using microscopy to image NFjB localisation in the cell.…”
Section: Effects Of B 2 -Ar Modulators On the Activity Of Nf-jb Subunitsmentioning
confidence: 99%
“…However, a number of other drugs, including inhaled steroids, β 2 agonists and leukotriene receptor antagonists, also reduce asthma exacerbations . Furthermore, inhaled steroids and β 2 agonists inhibit RV replication and the RV infection‐induced production of cytokines, as we previously reported . Therefore, careful attention is needed when considering the influence of the effects of these drugs in evaluations of the ability of L‐carbocisteine to prevent asthma exacerbation.…”
Section: Discussionmentioning
confidence: 90%